Gagasan Kampung Oksigen Pandanwangi sebagai Upaya Meningkatkan Kesadaran Masyarakat Peduli Lingkungan di Kota Malang - Aris Siswati; Dani Yuniawan (University of Merdeka Malang, 2021)
Population growth in Indonesia always increases every year. This has resulted in an increase in life support needs such as buildings, transportation, and others. If it is not balanced with the concept of sustainable development, it will cause problems for the environment. Indicators of environmental problems caused by population growth in each region are always different. Malang City is one of the cities experiencing population growth. One indicator of environmental problems in the city of Malang is an increase in the number of sufferers of acute respiratory infections (ARI) every year. Pandanwangi Village is one of the villages with the highest ARI disease spread apart from Kedungkandang and Mulyorejo. The solution to overcome these environmental problems is by carrying out “Kampung Oksigen” Oxygen Village Planning in Pandanwangi Village. The concept of a “Kampung Oksigen” that is realized is by multiplying plants such as Sansevieria and grapevines that have the ability to produce oxygen and absorb carbon dioxide produced by vehicles. The result of this service is in the form of a “Kampung Oksigen” gate equipped with a set of supporting plants to be a pilot for community efforts to participate in creating a healthy and beautiful environment.